PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH LINGKUNGAN KERJA, GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI: Studi Kasus di Badan Pendapatan Daerah Kabupaten Muna - Harmin Harmin; Samdin Samdin; Endro Sukotjo; Adnan Hakim; Muhammad Masri (Pascasarjana Universitas Halu Oleo, 2021)
This study aims to explain and examine the effect of the work environment, leadership style, organizational culture on job satisfaction and employee performance, job satisfaction on employee performance, then examine and explain the role of job satisfaction in mediating the influence work environment, leadership style, and organizational culture on employee performance. This research approach is survey with explanatory research design. The data was collected in a cross-sectional manner using an instrument in the form of a questionnaire. The population in this study were all 49 Civil Servants (PNS). The sampling technique is a saturated sample (census) where the entire population is used as the research sample. The data analysis technique to answer the research hypothesis is Partial Least Square (PLS).The results showed that the work environment had a significant effect on job satisfaction, but the work environment had no effect on employee performance, leadership style had a significant effect on job satisfaction and employee performance, organizational culture had a significant effect on job satisfaction and employee performance. Then job satisfaction had a significant effect on employee performance. In addition, the results of this study indicate that job satisfaction acts as a complete mediation the influence of the work environment on employee performance. Then job satisfaction does not mediate (no mediation) the influence of leadership style on employee performance. Furthermore, job satisfaction acts as a partial mediation the influence of organizational culture on employee performance.